ENHANCING INNOVATION AND SUSTAINABILITY REGIONAL TOURISM DEVELOPMENT IN THE ERA INDUSTRY 4.0 - Isdarmanto Isdarmanto; Christantius Dwiatmadja; Hari Sunarto; Antonius Suryo Abdi (Journal of Business on Hospitality and Tourism, 2020)
This study discusses how the sustainability tourism development strategy in every regency be able to improve the social welfare of local communities. The decentralization program has given freedom and policy to enhance the role of regional tourism to be more competitive. This study is using qualitative methods to be able to explore the empiric phenomenon of deeper problems that expected to be used as a reference for the strategy development of regional tourism applied in global and digital era, which is very competitive and professional through the strategy of well structure and systematic tourism program to be effective and efficient.